Colorado : a history of the Centennial State - Abbott, Carl, 1944- (University Press of Colorado, 2013)
Since 1976, newcomers and natives alike have learned about the rich history of Colorado from this book. In this fifth edition, the coauthors incorporate contemporary events, scholarship, and insights about the state in a book that general readers and students will enjoy. This edition tells of conflicts, shifting alliances, and changing ways of life as Hispanic, European, and African American settlers flooded into a region that was already home to Native Americans. Providing a balanced treatment of the entire state's history - from Grand Junction to Lamar and from Trinidad to Craig - the authors also reveal how Denver and its surrounding communities developed and gained influence. While continuing to elucidate the significant impact of mining, agriculture, manufacturing, and tourism on Colorado, this edition broadens and focuses its coverage by consolidating material on Native Americans into one chapter and adding a new chapter on sports history. The authors also expand their discussion of the twentieth century with updated sections on the environment, economy, politics, and cultural conflicts.